Poor Sleep Quality in Crohn's Disease Is Associated With Disease Activity and Risk for Hospitalization or Surgery. Issue 8 (10th December 2019) - Sofia, M Anthony; Lipowska, Anna M; Zmeter, Nada; Perez, Edgar; Kavitt, Robert; Rubin, David T
Abstract: Background and Aims: Poor sleep quality in Crohn's disease (CD) is associated with histologic activity and clinical relapse. We sought to characterize sleep dysfunction and determine the effect of poor sleep quality on risk for hospitalization and surgery. Methods: Clinical data were collected for CD subjects including the Pittsburgh Sleep Quality Index (PSQI) and Harvey-Bradshaw index (HBI). The PSQI score and a brief medical history were obtained for control subjects. The PSQI and HBI correlation was tested at an initial clinic visit and at follow-up. Crohn's disease subjects with and without poor sleep were compared for risk of hospitalization or surgery by Kaplan–Meier and Cox proportional hazards. Results: Ninety-two CD and 82 control subjects were included. Crohn's disease and control subjects shared similar baseline characteristics and PSQI (8.3 vs 7.8, P = 0.31), and 77% of the CD population had PSQI >5. Crohn's disease subjects with PSQI >5 more often had inflammatory phenotypes and reported increased benzodiazepine and psychiatric medication use. Crohn's disease subjects with PSQI >5 also reported more night awakenings due to pain and bathroom use. The PSQI correlated with HBI (r = 0.256, P = 0.014), and ΔPSQI on follow-up correlated with ΔHBI (r = 0.47, P = 0.002). Cox proportional hazards model for hospitalization or surgery showed that PSQI >8 was predictive of surgery or hospitalization (hazards ratio 5.37; 95% confidence interval, 1.39–27.54). Conclusion: There is a high burden of poor sleep quality in CD, which is associated with risk for adverse outcomes. Sleep quality may identify CD patients at risk for complications and have prognostic value in CD. Abstract : Outpatients with Crohn's disease have a high rate of sleep dysfunction using the Pittsburgh Sleep Quality Index. Sleep quality is sensitive to changes in disease activity, and poor sleep quality (PSQI >8) is independently associated with hospitalization or surgery.